Tyrosine Kinase Inhibitors in Pulmonary Arterial Hypertension: A Double-Edge Sword? - Godinas, Laurent; Guignabert, Christophe; Seferian, Andrei; Perros, Frederic; Bergot, Emmanuel; Sibille, Yves; Humbert, Marc; Montani, David (Seminars in Respiratory and Critical Care Medicine, 2013)
New treatments for pulmonary arterial hypertension (PAH) are a crucial need. The increased proliferation, migration, and survival of pulmonary vascular cells within the pulmonary artery wall in PAH have allowed successful transposition of pathophysiological elements from oncologic researches. Next steps will require translation of these biological advances in PAH therapeutic arsenal and guidelines. This review synthesizes recent data concerning the role of receptor tyrosine kinases and their inhibitors in PAH, with implications in animal models and humans. Results of clinical trials are now accumulating to establish beneficial role of tyrosine kinase inhibitors (TKIs) in PAH and further findings are expected in the near future. Beside this curative approach, evidences of a possible TKI-induced cardiotoxicity are emerging. These safety issues raise concern about a potential amplified harmful effect in PAH, a pathology characterized by an underlying cardiac dysfunction. In addition, analyses of PAH registries shed light on a selective pulmonary vascular toxicity triggered by TKIs, especially dasatinib. These possible dual effects of the TKIs in PAH need to be taken in account for future pharmacological development of this therapeutic class in PAH.
Keywords: pulmonary arterial hypertension; receptor tyrosine kinase; imatinib; sorafenib; dasatinib; cardiotoxicity